A Feasibility of Flexible Learning Program on Social Networks for Prospective Science Teachers - Vetsawat, Chanarak; Nuangchalerm, Prasart; Prachagool, Veena; Dostal, Jiri (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2024)
The innovative skills in designing effective lessons for both students and teachers through social networks is very crucial for modern classrooms. This study aimed to explore the novel and feasibility of flexible learning programs on social networks which are developed by researchers and for prospective science teachers. The program includes 5 main elements: 1) Program principles, 2) Program aims, 3) Program content, 4) Formats and activities used in the program, 5) Measurement and evaluation. The feasibility is explored at the highest level. In terms of content, technology, and pedagogy innovations, the exchange of information and resources made possible by the utilization of assets promotes new ideas and breakthroughs. The flexible learning program is new to implement in prospective science teachers and response to the professional standards.